EFL students - Metaria, Metaria; Cahyono, Bambang Yudi (Journal on English as a Foreign Language, 2024)
Nowadays, in the post-pandemic educational landscape, it is intriguing to investigate whether technological supports are still relevant and necessary. This article critically summarizes and reviews the effect of technology utilization on students' engagement presented in a study by Yu et al. (2022). Then, using a mixed-methods design, this study explored English as a foreign language (EFL) students